Sistem pendidikan di pondok pesantren RU Sakatiga dalam perspektif nilai-nilai pendidikan multikultural - Mulyani, Sri; Afriantoni,; Afgani, Muhammad Win (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2024)
Indonesian society is a society with a very complex level of diversity, a society with this diversity is known as a multicultural society. In the diversity of Indonesian society, education regarding multicultural education is very necessary. The content of multicultural educational values at the Raudhatul Ulum Islamic Boarding School includes the Raudhatul Ulum Islamic Boarding School having the principle of "Standing above for all groups and not taking sides with certain groups". This principle is intended not to discriminate against the background of students who wish to study at the Raudhatul Ulum Islamic Boarding School. The research objective in this study is to analyze the description of the vision, mission and educational goals as well as the curriculum and learning methods at the Raudhatul Ulum Islamic Boarding School from the perspective of multicultural educational values. The research results show that the multicultural education values contained in the vision, mission and objectives of the Raudhatul Ulum Islamic Boarding School are human values, equality values, justice values, the value of recognizing, accepting and appreciating diversity and the value of peace. The values of multicultural education contained in the curriculum and learning methods within the Raudhatul Ulum Islamic Boarding School are the value of democracy, the value of equality, the value of justice, the value of recognizing, accepting and appreciating diversity and the value of peace. Abstrak Masyarakat Indonesia merupakan masyarakat dengan tingkat keanekaragaman yang sangat kompleks, masyarakat dengan keanekaragaman tersebut dikenal dengan istilah masyarakat multikultural. Dalam keberagaman masyarakat Indonesia ini, maka sangatlah diperlukannya pendidikan mengenai pendidikan multikultural. Adapun muatan nilai-nilai pendidikan multikultural pada Pondok Pesantren Raudhatul Ulum di antaranya yaitu Pondok Pesantren Raudhatul Ulum ini memiliki prinsip “Berdiri di atas untuk semua golongan dan tidak memihak kepada golongan tertentu”. Prinsip ini dimaksudkan untuk tidak membeda-bedakan terhadap latar belakang santri yang ingin menimba ilmu di Pondok Pesantren Raudhatul Ulum tersebut. Tujuan penelitian dalam penelitian ini adalah untuk menganalisis deskripsi visi, misi dan tujuan pendidikan serta kurikulum dan metode pembelajaran di Pondok Pesantren Raudhatul Ulum dalam perspektif nilai-nilai pendidikan multikultural. Hasil penelitian menunjukkan bahwa nilai-nilai pendidikan multikultural yang terkandung di dalam visi, misi dan tujuan Pondok Pesantren Raudhatul Ulum adalah nilai kemanusiaan, nilai kesetaraan, nilai keadilan, nilai mengakui, menerima dan menghargai keragaman serta nilai kedamaian. Nilai-nilai pendidikan multikultural yang terkandung di dalam kurikulum dan metode pembelajaran di dalam lingkungan Pondok Pesantren Raudhatul Ulum adalah nilai demokrasi, nilai kesetaraan, nilai keadilan, nilai mengakui, menerima dan menghargai keragaman serta nilai kedamaian.